(untitled) (Our Nature, 2025)
Present study reveals the existence of 61 species of indigenous freshwater ornamental fish under 38 genera, 24 families of 8 Orders. A thorough survey has been conducted from April 2018 to December 2022 on the subject under study and achieved the aforesaid results. Main objectives of the current investigation are to collect, identify and narrate conservation strategies for indigenous freshwater ornamental fish species of undivided Paschim Medinipur. Present contribution enlisted the up to date the freshwater ornamental fish faunal diversity of the study area. The work will certainly be helpful to the fishery managers, researchers and aquaculturists for their future planning.